Sōseki : modern Japan's greatest novelist - Nathan, John, 1940- (Asia perspectives., 2018)
John Nathan provides a lucid and vivid account of Natsume Sōseki, the father of the modern novel in Japan. This biography elevates Sōseki to his rightful place as a great synthesizer of literary traditions and a brilliant chronicler of universal experience who, no less than his Western contemporaries, anticipated twentieth-century modernism.